'I am pleased to shop somewhere that is fighting the supermarkets a little bit'. A cultural political economy of alternative food networks. Issue 91 (May 2018) - Watts, David; Little, Jo; Ilbery, Brian
Highlights: Cultural political economy (CPE) can be used to analyse subaltern imaginaries. Using CPE puts alternative food networks on firmer ontological and normative bases. Conventionalisation is not unidirectional: it can change the dominant dispositive. Local emerges as a scale of unmediated interaction, rather than referring to places. Abstract: This paper conducts a cultural political economy (CPE) analysis of consumers' semiotic and material construals of alternative food networks (AFN). It starts by outlining, in the context of debate over AFN, why CPE is a useful analytical tool. The collection of talk data from 40 respondents, and food consumption data from 20 respondents, is outlined and explained. Talk data reveal that interviewees construe conventional and alternative food networks differently based on values relating to food quality judgements, provenance and trust, and alternativeness. Consumption data demonstrate respondents' material engagement with conventional and, to a lesser extent, alternative food networks. The paper concludes that CPE is a productive framework for analysing AFN qua a subaltern economic imaginary, and that it can help to set them on 'firmer' ground, both ontologically and normatively.